Electrical stimulation tracking control for paraplegic patients using T–S fuzzy models - Gaino, R.; Covacic, M. R.; Teixeira, M. C M [UNESP]; Cardim, R. [UNESP]; Assunção, E. [UNESP]; de Carvalho, A. A. [UNESP]; Sanches, M. A A [UNESP] (Elsevier, 2017)
This paper presents the design and simulation results considering the use of functional electrical stimulation to control the leg position of paraplegic patients. The plant is described by a nonlinear system using Takagi–Sugeno fuzzy models and a closed-loop control is presented. A transfer function represents the mathematical model related to the muscle torque and the electrical stimulation pulse width. Considering that, during the operation, the leg position is between 0° and 60°, then two fuzzy regulators were designed, assuming that the state vector is available or using an observer when only the output is available. This design was based on the Lyapunov stability theory and Linear Matrix Inequalities (LMIs). The simulation results show that the proposed procedures are efficient and offer good results for this control problem. Finally, new conditions regarding the design of the output tracking control, using a suitable nonlinear transformation for the description of the plant in an adequate form, is presented.
Keywords: Control of leg position; Functional electric stimulation; LMI; Paraplegic patients; State regulator; Tracking control; T–S fuzzy models